A higher-order method for nonlinear singular two-point boundary value problems - K. M. Furati; M. A. El-Gebeily (International Journal of Mathematics and Mathematical Sciences)
We present a finite difference method for a general class of nonlinear singular two-point boundary value problems. The order of convergence of the method for such a general class of problems is higher than the previous reported methods. The method yields a fourth-order convergence for the special case p(x)=w(x)=xα, α≥1.